Application of the Qowaid wa Al-Tarjamah Method in Arabic Learning in Grade 7 Madrasah Sanawiah in Jember Regency - Muhammad Hasbi Ash Shidiki; Doni Septi (Indonesian Journal of Islamic Studies, 2022)
This article aims to determine the application of the Qowaid wa al-Tarjamah method in learning Arabic in 7th grade MTs. Al-Misri Rambi Puji – Jember. This study uses a descriptive qualitative approach whose data is obtained from a detailed study of a single background, a single subject, or a particular event. The results showed that, the application of the Qowaid wa al-Tarjamah method in learning Arabic in 7th grade MTs. Al-Misri Rambi Puji – Jember has 3 stages, namely preparation, implementation and evaluation of the application of the Qowaid wa al-Tarjamah method in learning Arabic.